SOSIALISASI KONSEP MANAJEMEN SUMBERDAYA BUDAYA PADA MASYARAKAT DESA HUTAN SEBAGAI UPAYA PELESTARIAN KAWASAN CAGAR BUDAYA PENANGGUNGAN - Reza Hudiyanto; Ismail Lutfi (Universitas Negeri Malang, 2021)
Cultural remain of the Hindu Buddhist period in Java from the 8th to 15th centuries AD representing cultural diversity in Indonesia. The existence of monuments is often being ignored by the local population for their minimal economic contribution. Practically, it caused a lot of damage to cultural heritage both caused by humans and nature. Therefore, the publishing of the Cultural Heritage Law and the management of cultural resources were carried out in villages located in the area closest to the Penanggungan Cultural Heritage Area. This activity was conducted by compelling most relevant information, drafting in easier grasping text, and selecting obtained feedback from the target group. Published material covers the history of the Penanggungan Temple Area, technical assistance and examples of cultural resource management in Trowulan. From this activity, it can be resumed that the public only have very tiny information about the opportunity offered by managing this the legacy of the Ancient Hindu State Majapahit. Both of these activities need to be followed byassistance and the formation of a main group. This main groups were driving force which has equipped with knowledge of social empowerment, a lot of material with regard to tourism on specific themes, environmental preservation and implementation of the mandate of the Law on Cultural Heritage. By knowing the important of temple, statue and monument in Penanggungan, it has proved increased their sense of preserving cultural heritage.